1992
DOI: 10.1083/jcb.117.6.1231
|View full text |Cite
|
Sign up to set email alerts
|

Release of myosin II from the membrane-cytoskeleton of Dictyostelium discoideum mediated by heavy-chain phosphorylation at the foci within the cortical actin network

Abstract: Abstract. Membrane-cytoskeletons were prepared from Dictyostelium amebas, and networks of actin and myosin II filaments were visualized on the exposed cytoplasmic surfaces of the cell membranes by fluorescence staining (Yumura, S., and T. . Cell . Addition of ATP caused contraction of the cytoskeleton with aggregation of part of actin into several foci within the network, but most of myosin II was released via the foci. However, in the presence of 10 mM MgCI2, which stabilized myosin II filaments, myosin II re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
(49 reference statements)
3
28
0
Order By: Relevance
“…Stimulation by cAMP results in dissociation of myosin II from the cytoskeleton and increase in MHC phosphorylation, possibly as a result of cAMP-induced MHC-PKC translocation to the membrane and phosphorylation of the cortical myosin II. These results are consistent with the results reported by Yumura and Kitanishi-Yumura (31), which indicate that during contraction, the myosin II that have moved toward the foci are phosphorylated by a specific MHCK that is localized at the foci, with the resultant disassembly of filaments which are finally released from membrane cytoskeleton.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Stimulation by cAMP results in dissociation of myosin II from the cytoskeleton and increase in MHC phosphorylation, possibly as a result of cAMP-induced MHC-PKC translocation to the membrane and phosphorylation of the cortical myosin II. These results are consistent with the results reported by Yumura and Kitanishi-Yumura (31), which indicate that during contraction, the myosin II that have moved toward the foci are phosphorylated by a specific MHCK that is localized at the foci, with the resultant disassembly of filaments which are finally released from membrane cytoskeleton.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to MHC-PKC, several other MHCKs have been identified in Dictyostelium (8,29,30 Overexpression of MHC-PKC resulted in highly phosphorylated MHC that does not represent new phosphorylation sites. MHC-PKC phosphorylates four sites on MHC in vitro (9); nevertheless, the in vivo levels of phosphate incorporation into MHC are very low (0.05 mol of phosphate/mol of MHC) (3,31). It was proposed that incorporation of a single phosphate to a single myosin II filament is enough for filament disassembly (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When number of actin foci began to increase, filaments of myosin II decreased in number. In a previous study, it was shown that myosin II is gathered at the actin foci and released from intact membrane-cytoskeletons when ATP is applied (31). In that study, it was demonstrated that myosin II was phosphorylated at the actin foci, disassembled to monomers,and released from the membrane.…”
Section: Discussionmentioning
confidence: 97%
“…58 The term remodeling is used in a general sense, including bending and buckling of the actin filaments (due to their low flexural rigidity [59][60][61] ), the possible redistribution of the cross-links and depolymerization of filaments along which the myosin heads slide. In our experiments, the actin filaments were stabilized by 0.5% polyethylene glycol in the medium 62 and the time required for the contraction of the wt cytoskeletons on a low adhesiveness substrate was of the order of 15 s, i.e.…”
Section: The Density Of Myosin Molecules Actively Driving the Contracmentioning
confidence: 99%